PENGEMBANGAN MEDIA NABATA (NAMA BANGUN DATAR) BERBASIS ARTICULATE STORYLINE MATERI MENGANAL BANGUN DATAR UNTUK SISWA KELAS II SEKOLAH DASAR - Siti Nikmathul Fitriyah; Sahari, Sutrisno; Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to (1) determine the validity of NABATA media based on articulate storyline for the material of recognizing flat shapes for grade II Elementary School students, (2) determine the practicality of NABATA media based on articulate storyline for the material of recognizing flat shapes for grade II Elementary School students, (3) determine the effectiveness of NABATA media based on articulate storyline for the material of recognizing flat shapes for grade II Elementary School students. The method used in this study is Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The data analysis method in this study includes validity testing, practicality testing, and effectiveness testing of NABATA media. Based on the validation results by material experts, this media obtained a percentage score of 86%, which is categorized as very valid. Validation from media experts showed a score of 84%, also with the criteria of very valid. For the practicality aspect, the assessment from the teacher questionnaire produced a percentage score of 90%, which is categorized as very practical. In addition, the student respondent questionnaire in the limited-scale trial obtained a score of 84% with a very practical category, while in the large-scale trial, the score obtained reached 92.8%, also in the very practical category. As for the effectiveness test, this media received a percentage score of 90%, which indicates a very effective category. Thus, the NABATA (Flat Building Name) media based on articulate storyline has proven to be very valid, very practical, and very effective to be used as a supporting media in Mathematics learning.